Medelling aspect of corrosive wear under biodiesel - Adebisi, Adetayo A.; Maleque, Md. Abdul (2011)
Biodiesel as an alternative renewable fuel is increasingly been considered as blending components or replacement for conventional petroleum fuel. Although the acceptability of biodiesel in automotive application is relatively a successful story, it is an issue with regards to its materials incompatibility. When compared to diesel, biodiesel is more prone to absorb water and allows the development of electrochemical corrosion. Corrosive wear occurs as a result of chemical reaction on wearing surface. The main aim of this paper is to study the modelling aspect of corrosive wear under biodiesel for automotive application. A systematic review analysis was performed on the corrosive wear, wear of engine component materials using on road engine test, aspect of corrosive wear and also factors affecting corrosive wear of automotive component. A corrosive wear model has been developed with three main domains such as mechanical wear, electrochemical corrosion, and interaction of both processes to evaluate the total corrosive wear of automotive component materials under biodiesel. It was found that modelling aspect play an important role in the measurement of corrosive wear especially under biodiesel. Keywords: Modelling, corrosive wear, automotive material.